Leadership and Career Development on Organizational Commitment and its Impact on the Performance of Employees PT. Bank Mandiri (Persero) Tbk Area Makassar Kartini - Natalia Sampe; Nurdin Brasit; Nurdjanah Hamid (PINISI Discretion Review, 2023)
A good organization that grows and develops will focus on human resources to carry out their functions optimally. Human resources are the resource that most determines the success of an organization that has made a large investment in developing the quality of its human resources in addition to investing in information technology. What is the relationship between leadership and career development to employee performance through organizational commitment? There are still few researchers who explore this question. The design of this study uses the survey method. This research was conducted at PT. Bank Mandiri (Persero) Tbk Makassar Kartini area. Data collection methods used in this study were questionnaires, documentation techniques and library techniques. The population of this study are permanent employees of PT. Bank Mandiri (Persero) Tbk Makassar Kartini area of 452 employees. Determination of the number of samples was carried out using the formula from Slovin, so that a total sample of 82 people was obtained. The analysis technique used is path analysis. The results showed that the leadership variables had a significant effect on organizational commitment. Career development has a significant effect on organizational commitment. Organizational commitment has a significant effect on employee performance. Leadership variable has a significant indirect effect on employee performance through organizational commitment, and career development has a significant indirect effect on employee performance through organizational commitment.